THE ROLE OF OMNICHANNEL SERVICE ON LATENT CONSUMER BEHAVIOR WITH PERCEIVED VALUE AS AN INTERVENING VARIABLE AT CV EMPAT CAHAYA NOESANTARA - Shinta Khusnatul Fadilah; Ignatia Martha Hendrati; Sugeng Purwanto (RADJA PUBLIKA, 2026)
This study aims to analyze the role of Omnichannel Service in activating Latent Consumer Behavior with Perceived Value as an intervening variable at CV Empat Cahaya Noesantara. The research is based on the issue of increasing consumer interactions across digital channels that are not matched by actual conversion from latent consumers into active customers, highlighting the need to understand how Omnichannel Service shapes consumers’ Perceived Value. The research uses a quantitative method with Partial Least Squares–Structural Equation Modeling (PLS-SEM). The sample consists of digital channel users of CV Empat Cahaya Noesantara who have interacted with the platform but have not completed or rarely engaged in transactions. Data were collected through an online questionnaire to examine both direct and indirect relationships among the variables. The results show that Omnichannel Service has a positive and significant effect on Perceived Value and Latent Consumer Behavior. Perceived Value also significantly influences Latent Consumer Behavior and mediates the relationship between Omnichannel Service and Latent Consumer Behavior. These findings emphasize the importance of channel integration, responsiveness, and information quality in enhancing Perceived Value and activating latent consumers.